2021
DOI: 10.1007/978-981-16-1866-6_40
|View full text |Cite
|
Sign up to set email alerts
|

A GUI to Analyze the Energy Consumption in Case of Static and Dynamic Nodes in WSN

Abstract: Wireless sensor networks consist of spatially dispersed sensors for monitoring physical parameters in various applications and in organizing the collected data at centralized location. These days, energy is one of the main factors that need to be intelligently consumed in wireless sensor networks. Techniques which can perform energy efficient clustering are required to maintain reliable sensing. In this paper, we consider both static and dynamic nodes. For static nodes, direct communication and low energy adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The requirement of a WSN is to achieve an energy efficient WSN with improved network lifetime [30], [31]. Even though many optimization techniques and algorithms are implemented [32], still there exists a need to identify more energy efficient algorithms for WSN with duty cycle approach.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of a WSN is to achieve an energy efficient WSN with improved network lifetime [30], [31]. Even though many optimization techniques and algorithms are implemented [32], still there exists a need to identify more energy efficient algorithms for WSN with duty cycle approach.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that MATLAB helps in providing accurate simulation details for the network. Sagare et al [20] showed a basic understanding of the use of clustering and the role of probability in selecting the cluster head.…”
Section: Introductionmentioning
confidence: 99%